Special Challenges and Opportunities in the (Equity) Financing of Protech Start-Ups - Tobias SICK; Harald BEHRSCHMIDT (Communications of International Proceedings, 2024)
This paper analyzes the difficulties that PropTech start-ups face in raising capital by utilizing equity financing as a source of finance. PropTech is an intrinsic marriage of technology and real estate in a single platform, making this platform very demanding and hugely capital-intensive for procurement, adaptation to new ideas, and intensification. Current research fails to provide in-depth information on the financial circumstances of the PropTech startups, presenting a gap for research. Several startups have succeeded in striking a balance by exploring opportunities in smart partnerships and using advanced technology to accelerate processes and investor networks. Government grants and tax concessions are useful tools that can be used to lighten the financial stress and the promoting of innovations. Looking at digital trends, investments like Airbnb, WeWork, and Compass companies can guide to efficiently adapt to challenges and conserve leadership in the global markets. While equity financing presents significant opportunities and challenges for PropTech start-ups, those that effectively leverage these strategies can achieve sustainable growth and success in a competitive market. Through the implementation of the literature review, case studies, and expert opinion techniques, this research closely explores the topic of equity financing for PropTech companies. The findings suggest introducing investors into strategic partnerships they need, promoting credibility among stakeholders, providing a means of raising funds, and ease of exit strategies. Still, on the contrary, it also brings to light the challenges of ownership dilution risk, complex valuations, and high investor expectations.
Keywords: PropTech start-ups; equity financing